2017
DOI: 10.1016/j.precamres.2017.07.036
|View full text |Cite
|
Sign up to set email alerts
|

The geochronological evolution of the Paleoproterozoic Baoulé-Mossi domain of the Southern West African Craton

Abstract: Generation and emplacement of felsic magmas in the Paleoproterozoic Baoulé-Mossi domain of the West African Craton does not match the apparent peaks of global crust generation identified between ca. 2900-2600, 1900-1600 and 1200-900 Ma. In contrast, across the Baoulé-Mossi domain, the emplacement of felsic intrusions ranges from ca. 2300 to 2000 Ma. It has proven difficult to place this magmatism within a robust geodynamic framework due to the lack of accurate geochronological data from across the West African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 85 publications
(37 reference statements)
6
31
0
Order By: Relevance
“…In previous studies, Cambrian–Ordovician successions along the northern Gondwana margin from Morocco in the west to Jordan in the east show prominent zircon groups between 750 and 530 Ma (Figure 7), with varying individual age peaks, including 1,100–950 Ma, 2,150–1,750 Ma, and 2,700–2,500 Ma (Meinhold et al, 2013). In this study, the ~618 Ma dominant age peak of the Ougarta Cambrian sandstone samples is consistent with the 750–530 Ma age peak identified in the WAC (Abati et al, 2012; Linnemann et al, 2011; Linnemann, Gerdes, Hofmann, & Marko, 2014; Parra‐Avila et al, 2017; Petersson, Schersten, Kristinsdottir, Kemp, & Whitehouse, 2018), and the secondary age peak of 2,035 Ma is consistent with the age of the Eburnean orogen in the WAC (Grenholm, Jessell, & Thébaud, 2019; Ikenne, Souhassou, Arai, & Soulaimani, 2017; Linnemann et al, 2011). Thus, the data from the Ougarta are consistent with proximal provenance from the WAC.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, Cambrian–Ordovician successions along the northern Gondwana margin from Morocco in the west to Jordan in the east show prominent zircon groups between 750 and 530 Ma (Figure 7), with varying individual age peaks, including 1,100–950 Ma, 2,150–1,750 Ma, and 2,700–2,500 Ma (Meinhold et al, 2013). In this study, the ~618 Ma dominant age peak of the Ougarta Cambrian sandstone samples is consistent with the 750–530 Ma age peak identified in the WAC (Abati et al, 2012; Linnemann et al, 2011; Linnemann, Gerdes, Hofmann, & Marko, 2014; Parra‐Avila et al, 2017; Petersson, Schersten, Kristinsdottir, Kemp, & Whitehouse, 2018), and the secondary age peak of 2,035 Ma is consistent with the age of the Eburnean orogen in the WAC (Grenholm, Jessell, & Thébaud, 2019; Ikenne, Souhassou, Arai, & Soulaimani, 2017; Linnemann et al, 2011). Thus, the data from the Ougarta are consistent with proximal provenance from the WAC.…”
Section: Discussionsupporting
confidence: 89%
“…As implicit in its name, this orogeny spans, like the Pan‐African/Brasiliano orogen, the Atlantic Ocean (e.g., Feybesse et al, 1998; Ledru, Johan, Milési, & Tegyey, 1994; Lerouge et al, 2006; Trompette, 1994). It encompasses the whole WCAFB (e.g., Feybesse et al, 1998; Lerouge et al, 2006; Loose & Schenk, 2018; Toteu et al, 1994), its South American equivalents, such as the Eastern Bahia and Mineiro belts (e.g., Aguilar et al, 2017; Alkmim & Wilson, 2017; Barbosa & Barbosa, 2017; Carvalho, Janasi, & Sayer, 2017), and its West African counterparts, the Ashanti‐Kumasi, Houndé, Lawra, Kédougou, Ouago‐Fitini, and Reguibat belts (e.g., Kouamelan et al, 1997; Lambert‐Smith et al, 2015; Parra‐Avila et al, 2017; Peucat et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It stretches across Cameroon, the Central African Republic, Equatorial Guinea, and Gabon, forming the West Central African Fold Belt (WCAFB; Boniface, Schenk, & Appel, 2012; Houketchang Bouyo, Pénaye, Mouri, & Toteu, 2019; Feybesse et al, 1998; Loose & Schenk, 2018; Nga Essomba et al, 2019; Thiéblemont, Callec, Fernandez‐Alonso, & Chène, 2018). Units equivalent to the Nyong Complex were mapped around the West African Shield, notably the Ashanti‐Kumasi, Houndé, Lawra, Kédougou, Ouago‐Fitini, and Reguibat belts (Kouamelan, Delor, & Peucat, 1997; Lambert‐Smith, Lawrence, Müller, & Treloar, 2015; Parra‐Avila et al, 2017; Peucat, Capdevila, Drareni, Mahdjoub, & Kahoui, 2005), and around the São Francisco Shield in Brazil, comprising the Eastern Bahia and Mineiro belts (Figure 1a; e.g., Aguilar et al, 2017; Alkmim & Wilson, 2017; Barbosa & Barbosa, 2017; Lopez, Cameron, & Jones, 2001; Neves et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of Archean zircons in the region therefore argues for greater interaction between the Baoulé-Mossi domain and the Archean Kénéma-Man domain. Additionally, zircon U-Pb dating and Hf and O-isotope studies of igneous rocks from the Palaeoproterozoic Baoulé-Mossi domain of the WAC, covering Burkina Faso, Ghana, Guinea and Mali, revealed the juvenile isotopic character of the domain, and further showed that the southern part of the WAC evolved by accretionary processes (Parra-Avila et al 2017. Similar to the above, zircon U-Pb age and Lu-Hf isotopic data from granites of southern, southeastern and northwestern Ghana suggest juvenile crustal addition with a short period of reworking of Archaean crust within the Palaeoproterozoic Birimian Terrane of Ghana, and provides evidence of subductionrelated crustal growth (Petersson et al 2016(Petersson et al , 2018.…”
Section: Introductionmentioning
confidence: 95%